Debt Sustainability and Sovereign Debt Crises: Assess the Challenges of Debt Sustainability Faced by Governments, Particularly in Emerging Markets, And the Risk of Sovereign Debt Crises, Including Debt Restructuring, Default Scenarios, And the Role of Int - Jo’rayev Og’abek (Genius Journals, 2024)
The concept of debt sustainability has become a pressing concern for governments and economists worldwide, as the burden of sovereign debt has reached alarming proportions in many countries. The repercussions of unsustainable debt can be far-reaching, culminating in full-blown sovereign debt crises that can have devastating consequences for the economy, financial markets, and the general populace. This article will delve into the significance of debt sustainability, the causes and consequences of sovereign debt crises, and the strategies employed by governments to mitigate these risks.
Keywords: sustainability; debt crisis; potential risks